Synthesis and Antioxidant Activities of Novel 5-Chlorocurcumin, Complemented by Semiempirical Calculations - Ahmed A. Al-Amiery; Abdul Amir H. Kadhum; Hasan R. Obayes; Abu Bakar Mohamad (Bioinorganic Chemistry and Applications)
The novel curcumin derivative (1E,4Z,6E)-5-chloro-1,7-bis(4-hydroxy-3-methoxyphenyl)hepta-1,4,6-trien-3-one (5-chlorocurcumin) was prepared from natural curcumin. The newly synthesised compound was characterised by spectral studies (IR, 1H NMR, and 13C NMR). The free radical scavenging activity of 5-chlorocurcumin has been determined by measuring interaction with the stable free radical DPPH, and 5-chlorocurcumin has shown encouraging antioxidant activities. Theory calculations of the synthesised 5-chlorocurcumin were performed using molecular structures with optimised geometries. Molecular orbital calculations provided a detailed description of the orbitals, including spatial characteristics, nodal patterns, and the contributions of individual atoms.